Pleomorphic adenoma of the breast - Sonagli, Marina; Flora, Georgia Terra Lustre di; Domingos, Tábata Alves; Cardona, Vinicius Felipe; Carvalho, Solange Maria Torchia de; Osório, Cynthia Aparecida Bueno de Toledo; Makdissi, Fabiana Baroni Alves (Mastology, 2021)
Pleomorphic adenoma (PA) is a common tumor of the salivary gland, but rarely occurs in the breast. PA of the breast is a benign tumor that usually presents as a periareolar nodule. Core-needle biopsies may yield misdiagnosis with complex fibroadenoma, phyllodes tumor and metaplastic breast cancer due to the mixture of stromal and epithelial elements. We present a case of PA of the breast suspected after core-needle biopsy, but confirmed after surgical excision. The importance to make a correct diagnosis consists in avoid extensive unnecessary surgery, such as mastectomy, since PA can be treated with local surgical resection.